Effect of nitrogen levels and biofertilizers on growth and yield of pearl millet (Pennisetum glaucum L.) under north western Rajasthan - ., Rinku; Shekhawat, P.S.; Kumawat, N.; Rathore, P.S.; Yadav, P. K.; Om, Hari (Annals of Agricultural Research, 2016)
The field experiment was conducted atÂ Research Farm, College of Agriculture Bikaner,Swami Keshwanand Rajasthan AgricultureÂ University, Bikaner.The maximum grain and stover yield were obtained under 40 kg N/ha which was at par with 20 kg N/ha and significantly superior to control. This treatment gave 24.97 and 17.57 per cent higher grain and stover yield over control, respectively. Harvest index did not influenced by nitrogen levels.Significantly highest grain (2267 kg/ha) and stover (3636 kg/ha) yield were obtained with Azotobacter + PSB, whereas, lowest grain (1653 kg/ha) and stover (3050 kg/ha) yield under no biofertilizers treatment.Conclusion may be drawn, dose of 40 kgN/ha and seed inoculation with Azotobacter + PSB enhance growth, yield attributes and yield of pearl millet.